Expo Milano 2015: The Overview, Issue, and Future for Agricultural Communicators - Abigail Borron; Jessica Holt (Journal of Applied Communications, 2016)
Expo Milano 2015 was an international agricultural event to promote and discuss the issue of food sustainability around the world. Two agricultural communication researchers attended the event in summer 2015 to better understand the world’s perspective of the prominent issues facing the agricultural industry and how other countries were addressing the issues. The Expo took place in Milan, Italy, and featured 140 countries and their perception on agriculture and food in their respective country. While the event was impressive, the issues purported to be the focus of the event (agriculture sustainability and food insecurity) were rarely addressed in each country. Rather, the countries focused on culture and how food impacted their culture and customs. Events like these offer agricultural communicators the opportunity to join the discussion of how the issues of food sustainability and insecurity can be positively impacted by agriculture technology and research; however, it may be only through the formation of meaningful and collaborative relationships with groups and organizations outside of the traditional agricultural industry that agricultural communicators will be invited to join the conversation. These relationships may need to be cultivated to show respect and mutual bene t for both the organization and the agricultural industry for long-term impact for the expansion of opportunities for agricultural communicators.
Keywords: Agriculture Sustainability; Expo Milano 2015; Worldwide Agriculture